A new species of Passiflora (Passifloraceae) from Mato Grosso do Sul, Brazil - Cervi, Armando Carlos; Imig, Daniela Cristina (Phytotaxa, 2013)
In this study we describe and illustrate Passiflora pottiae, a new species from Mato Grosso do Sul, Brazil. Passiflora pottiae belongs to Passiflora subgenus Passiflora supersection Stipulata section Granadillastrum.